Pembuatan dan Pengujian Stabilitas Bubuk Pewarna Alami dari Daun Bayam Merah (Alternanthera amoena Voss.) - Permatasari, Niken Ayu; Afifah, Fitri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 3 (2020): September, 2020)
Redleaf amarant (Alternanthera amoena Voss.) is a kind of leaf that used as natural dye because its composition consists anthocyanin which produce red color in low pH condition. The aims of this research was to produce natural dye powder from readleaf amaranth and to test its stabilized during the storage. The experimental design that used Completed Randomized Design (CRD) with two factors were  concentration of maltodextrin (15%, 20%, 25%) and the solvent (aquadest, aquadest+HCl 1%, aquadest+ citric acid 5%). The result showed that the best treatment of natural dye powder from redleaf amaranth was found in the addition of maltodextrin concentration of 15% and aquadest+citric acid 5% with resulted in yield of 15,69%, moisture content 4,36%, total anthocyanin 0,587 mg/g substance, 99,00% of solubility, and   0 Hue  6, 34  (red-purple). The higher concentrations of maltodextrin caused higher yield and solubility that resulted, the lower moisture content and total of anthocyanin, and also paler color that resulted. The testing of the stability of natural dye powder to light, pH, and temperature produces a good stability and a less significant quality reduction until day 10. The longer the storage caused higher moisture content, the lower solubility and total antocyanin, and paler color that resulted. Key words:  anthocyanin, maltodextrin, natural dye powder, redleaf a marant